2014
DOI: 10.1007/s00248-014-0448-8
|View full text |Cite
|
Sign up to set email alerts
|

High Fungal Diversity and Abundance Recovered in the Deep-Sea Sediments of the Pacific Ocean

Abstract: Knowledge about the presence and ecological significance of bacteria and archaea in the deep-sea environments has been well recognized, but the eukaryotic microorganisms, such as fungi, have rarely been reported. The present study investigated the composition and abundance of fungal community in the deep-sea sediments of the Pacific Ocean. In this study, a total of 1,947 internal transcribed spacer (ITS) regions of fungal rRNA gene clones were recovered from five sediment samples at the Pacific Ocean (water de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 44 publications
8
62
0
Order By: Relevance
“…Among the Basidiomycota, Agaricomycetes were the most frequently recovered, with isolates being affiliated with Bjerkandera spp., Sistotrema brinkmannii, Trametes versicolor, and uncultured Agaricomycetes. Although the cultivable representatives of Agaricomycetes appear to be rare in marine environments (36), the molecular signatures of Agaricomycetes have been detected in deep-sea environments (3,9,11,45) and Agaricomycetes have been identified to be the dominant fungal class in mangrove habitats (46).…”
Section: Discussionmentioning
confidence: 99%
“…Among the Basidiomycota, Agaricomycetes were the most frequently recovered, with isolates being affiliated with Bjerkandera spp., Sistotrema brinkmannii, Trametes versicolor, and uncultured Agaricomycetes. Although the cultivable representatives of Agaricomycetes appear to be rare in marine environments (36), the molecular signatures of Agaricomycetes have been detected in deep-sea environments (3,9,11,45) and Agaricomycetes have been identified to be the dominant fungal class in mangrove habitats (46).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2014) used a similar Q-PCR-based approach to quantify fungi in sediment samples collected from five deep-sea sites in the Pacific Ocean and showed that Fungi-specific 28S rRNA gene copies ranged from 3.5 × 10 6 to 5.2 × 10 7 copies per g wet sediment (Xu et al, 2014). Assuming that 1 g sediment≈1 ml seawater, then as with bacteria in sediments and bacterioplankton, fungi in sediments occur at higher abundances than mycoplankton in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fungi are abundant in marine sediments (Orsi et al, 2013a, b;Xu et al, 2014;Taylor and Cunliffe, 2015). Xu et al (2014) used a similar Q-PCR-based approach to quantify fungi in sediment samples collected from five deep-sea sites in the Pacific Ocean and showed that Fungi-specific 28S rRNA gene copies ranged from 3.5 × 10 6 to 5.2 × 10 7 copies per g wet sediment (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on the microbial biodiversity of deep sea sponges sampled at depths of between 760 and 2900 m below sea level, indicating that the microbial community structures of these sponges may represent an untapped source of potential microbial biodiversity [25,26]. Bacterial and fungal communities from deep sea sediments also continue to receive attention, not only from an ecological standpoint [27], but also due to the ability of microorganisms isolated from this ecosystem to produce novel bioactive molecules [28,29] and enzymes of biotechnological importance [30,31]. Cold-active enzymes are of particular interest as they possess a range of structural features that promote flexibility at the active site, low substrate affinity, and high specific activity at low temperatures.…”
Section: Introductionmentioning
confidence: 99%